Clinical Events After Deferral of LAD Revascularization Following Physiological Coronary Assessment. - Sen, S (2019)
BACKGROUND: Physicians are not always comfortable deferring treatment of a stenosis in the left anterior descending (LAD) artery because of the perception that there is a high risk of major adverse cardiac events (MACE). The authors describe, using the DEFINE-FLAIR (Functional Lesion Assessment of Intermediate Stenosis to Guide Revascularisation) trial, MACE rates when LAD lesions are deferred, guided by physiological assessment using fractional flow reserve (FFR) or the instantaneous wave-free ratio (iFR). OBJECTIVES: The purpose of this study was to establish the safety of deferring treatment in the LAD using FFR or iFR within the DEFINE-FLAIR trial. METHODS: MACE rates at 1 year were compared between groups (iFR and FFR) in patients whose physiological assessment led to LAD lesions being deferred. MACE was defined as a composite of cardiovascular death, myocardial infarction (MI), and unplanned revascularization at 1 year. Patients, and staff performing follow-up, were blinded to whether the decision was made with FFR or iFR. Outcomes were adjusted for age and sex. RESULTS: A total of 872 patients had lesions deferred in the LAD (421 guided by FFR, 451 guided by iFR). The event rate with iFR was significantly lower than with FFR (2.44% vs. 5.26%; adjusted HR: 0.46; 95% confidence interval [CI]: 0.22 to 0.95; p = 0.04). This was driven by significantly lower unplanned revascularization with iFR and numerically lower MI (unplanned revascularization: 2.22% iFR vs. 4.99% FFR; adjusted HR: 0.44; 95% CI: 0.21 to 0.93; p = 0.03; MI: 0.44% iFR vs. 2.14% FFR; adjusted HR: 0.23; 95% CI: 0.05 to 1.07; p = 0.06). CONCLUSIONS: iFR-guided deferral appears to be safe for patients with LAD lesions. Patients in whom iFR-guided deferral was performed had statistically significantly lower event rates than those with FFR-guided deferral.